Do feelings matter? The effect of leader affective presence on employee proactive customer service performance. Issue 7 (9th May 2020) - Jiang, Jing; Dong, Yanan; Li, Bin; Gu, Huimin; Yu, Larry
Abstract : Purpose: Applying affect-as-information theory, this research analyzed the relationship of leader affective presence and employee proactive customer service performance (PCSP) in hospitality organizations. It further explored when and how leader affective presence influenced employee PCSP. Design/methodology/approach: Taking a sample of 110 teams with 361 pairs of leaders and employees in Chinese hotels, a moderated mediation model was tested across individual and team levels using hierarchical linear modeling. Findings: This study found that leader positive affective presence (LPAP) had a positive effect on employee PCSP, whereas leader negative affective presence (LNAP) had a negative effect on employee PCSP. Employee prosocial motivation mediated the relationship between leader affective presence and employee PCSP. The employee power distance value weakened the LNAP–employee prosocial motivation relationship, which subsequently mitigated the negative indirect effect of LNAP on employee PCSP through employee prosocial motivation. Research limitations/implications: The sample was drawn from one hotel group in China, which may limit external validity. Practical implications: Hospitality organizations should emphasize the affective traits of leaders in employee initiatives. Leader affective presence should be considered during recruitment and promotion. Management should pay more attention to employee emotional management and value alignment. Originality/value: The findings provide deeper insight into the role of LPAP and LNAP in influencing employees' PCSP. It sheds new light on the mechanisms and conditions through which leader affective presence might heighten or hinder employee PCSP.